2020
DOI: 10.3842/sigma.2020.060
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Component Extension of CAC Systems

Abstract: In this paper an approach to generate multi-dimensionally consistent N -component systems is proposed. The approach starts from scalar multi-dimensionally consistent quadrilateral systems and makes use of the cyclic group. The obtained N -component systems inherit integrable features such as Bäcklund transformations and Lax pairs, and exhibit interesting aspects, such as nonlocal reductions. Higher order single component lattice equations (on larger stencils) and multi-component discrete Painlevé equations can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 58 publications
4
25
0
Order By: Relevance
“…and the resulting birational system will be called companion system. Now we are ready to prove that ( 15) is quadrirational provided that the centrality assumptions (19) are imposed. From ( 12) we obtain…”
Section: Notation Definitions and The Family Of Lax Matrices L Nkmentioning
confidence: 98%
See 3 more Smart Citations
“…and the resulting birational system will be called companion system. Now we are ready to prove that ( 15) is quadrirational provided that the centrality assumptions (19) are imposed. From ( 12) we obtain…”
Section: Notation Definitions and The Family Of Lax Matrices L Nkmentioning
confidence: 98%
“…The hierarchy of difference systems ( 15) is birational. If the centrality assumptions (19) are imposed, then (15) is quadrirational.…”
Section: Notation Definitions and The Family Of Lax Matrices L Nkmentioning
confidence: 99%
See 2 more Smart Citations
“…There was a little work on the nonlocal discrete integrable systems. In [19], Zhang et al investigated two types of nonlocal discrete integrable equations, which were constructed as reductions of 2-component Adler-Bobenko-Suris systems [20]. In particular, they showed that the 2[0, 1] Adler-Bobenko-Suris system allows reverse-n nonlocal reduction and the 2 [1,1] Adler-Bobenko-Suris system admits reverse-(n, m) nonlocal reduction.…”
Section: Introductionmentioning
confidence: 99%